2018
DOI: 10.1044/2018_jslhr-l-17-0132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interventions That Include Aided Augmentative and Alternative Communication Input on the Communication of Individuals With Complex Communication Needs: A Meta-Analysis

Abstract: https://doi.org/10.23641/asha.6394364.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…A range of studies have pointed out that an online community of practice provides opportunities to its members to become interactive participants (Agrawal & Snekkenes, 2017; Diep et al., 2016; Jesionkowska, 2020; Nuutinen & Filho, 2018). In addition to this, it has been generally acknowledged that these communities function as a catalyst for improving adults' engagement (O'Neill et al., 2018). According to Matzembacher et al.…”
Section: Research Backgroundmentioning
confidence: 99%
“…A range of studies have pointed out that an online community of practice provides opportunities to its members to become interactive participants (Agrawal & Snekkenes, 2017; Diep et al., 2016; Jesionkowska, 2020; Nuutinen & Filho, 2018). In addition to this, it has been generally acknowledged that these communities function as a catalyst for improving adults' engagement (O'Neill et al., 2018). According to Matzembacher et al.…”
Section: Research Backgroundmentioning
confidence: 99%
“…A long line of research has demonstrated that the way parents interact with their children can impact language development. For example, responding contingently to children's communication attempts has been associated with improved language outcomes for participants between the ages of 2 and 12 years learning to use augmentative and alternative communication (O'Neill et al, 2018). Conversely, 3-year-old children whose parents did not respond positively to their communication at age of 2 years have been found to have lower language levels (Hirsh-Pasek et al, 2015).…”
Section: Maternal Responsivity and Language Development In Fxsmentioning
confidence: 99%
“…Another key aspect for an effective interactive learning environment that supports the development of children with or without speech, language, or communication needs is the skills and performance of communication partners (Brinton and Fujiki, 2011;Romski et al, 2011;Kent-Walsh et al, 2015;Mermelshtine, 2017;Biggs et al, 2018;O'Neill et al, 2018). Partners must learn scaffolding strategies such as providing opportunities to talk and learn about emotions (making comments, asking questions, etc.…”
Section: Introductionmentioning
confidence: 99%